Efficacy of rice straw mulch for the sustainable production and insect pest management in okra (Abelmoschus esculentus) - SAHA, SWATI; CHANDRASHEKAR, K; SONKE, L R; MAHAPATRO, G K (The Indian Journal of Agricultural Sciences, 2020)
With an aim to utilize rice straw for crop mulching purpose and prevent environmental damage caused due to its burning, the efficacy of rice straw mulching was compared with the standard practice of silver colored polyethylene mulch and without mulch in okra (Abelmoschus esculentus (L.) Moench) for the crop growth, yield and for the reduction of insect pest population. The trials were performed during the rabi season with two sprays each of neem (Agroneem®@ 2 ml/l), imidacloprid (Confidor®@ 0.5 ml/l) and their combination. Plant growth and yield was significantly higher in silver mulch and straw mulch compared to the control. The yield of okra was maximum in silver colored polythene mulch along with the application of insecticide imidacloprid. The yield were 23.89, 16.08 and 15.80 t/ha respectively during the years, 2015-16, 2016-17 and 2017-18. The yield observed in straw mulch was slightly lower than silver colored polythene mulch, but higher than control. The straw mulch was found at par with silver colored polythene mulch in reducing population of sap sucking insect, pests, aphids, thrips, leafhoppers and whiteflies. Among the treatments, spray of imidacloprid (@ 0.5 ml/l) was found best for reducing pest population. The results indicated the utility of rice straw mulching as an organic option for the okra cultivation, which is otherwise burnt every year creating huge environmental problem in India